2016
DOI: 10.4040/jkan.2016.46.2.226
|View full text |Cite
|
Sign up to set email alerts
|

A Grounded Theory Approach on Nurses' Experience with Workplace Bullying

Abstract: Purpose: The purpose of this qualitative study was to explore the workplace bullying experience of Korean nurses. Methods: Participants were twenty current or former hospital nurses who had experienced workplace bullying. Data were collected through focus group and individual in-depth interviews from February to May, 2015. Theoretical sampling method was applied to the point of theoretical saturation. Transcribed interview contents were analyzed using Corbin and Strauss's grounded theory method. Results: A tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 17 publications
(7 reference statements)
0
12
0
3
Order By: Relevance
“…Interpersonal relationship has been reported as a key strategy to prevent workplace bullying [2][3][4][5]. In this study, we developed the CRP using nonviolent communication based on improving interpersonal relationship, and evaluated the effect of the CRP on interpersonal relationship, workplace bullying, symptom experience, and turnover intention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interpersonal relationship has been reported as a key strategy to prevent workplace bullying [2][3][4][5]. In this study, we developed the CRP using nonviolent communication based on improving interpersonal relationship, and evaluated the effect of the CRP on interpersonal relationship, workplace bullying, symptom experience, and turnover intention.…”
Section: Discussionmentioning
confidence: 99%
“…In this way, it helps in the development of positive interpersonal relationships [14]. We designed the present intervention based on the premise that bullying is preceded by problems in communication and interpersonal relationships [2]. However, it may also be that bullying causes problems in communication and interpersonal relationships: one study indicated that 55.8% of the use of scenarios to reduce workplace bullying among Canadian health care workers.…”
Section: Discussionmentioning
confidence: 99%
“…์ฃผ์š”์–ด: ๊ฐ„ํ˜ธ์กฐ์ง๋ฌธํ™”, ์—…๋ฌด์ˆ˜ํ–‰๋Šฅ๋ ฅ, ์ง์žฅ ๋‚ด ๊ดด๋กญํž˜ ๋ฏธํ•˜๋Š” ์šฉ์–ด๋ฅผ ํ˜ผ์šฉํ•˜์—ฌ ์‚ฌ์šฉํ•˜๋Š”๋ฐ ๊ตญ๋‚ด ์—ฐ๊ตฌ์—์„œ๋Š” ํฌ๊ฒŒ ์ง ์žฅ ๋‚ด ์•ฝ์ž ๊ดด๋กญํž˜ (Kang, Kim, & Han, 2018;Park et al, 2013) ๊ณผ ์ง์žฅ ๋‚ด ๊ดด๋กญํž˜ (Han & Ha, 2016;Im, Kim, & Kwon, 2016;Kang & Yun, 2016;Kim, 2015;Lee, Lee, & Bernstein, 2013;Lee, 2014;Lee, 2017;Park, 2017;Sim, Ahn, & Lee, 2018) (Han & Ha, 2016;Sim et al, 2018), ์‚ฌํšŒ์  ์ง€์ง€ (Han & Ha, 2016), ์ž์•„์กด์ค‘๊ฐ (Han & Ha, 2016)…”
unclassified
“…๊ฐ•์ง€์—ฐ โ€ค ์ด๋ฏผ์ฃผ ๊ดด๋กญํž˜์ด ํ”ํžˆ ๋ฐœ์ƒํ•œ๋‹ค [2]. 2015๋…„ ํ•œ๊ตญ์ง์—…๋Šฅ๋ ฅ๊ฐœ๋ฐœ์›์˜ ์ง ์ข…๋ณ„ ์ง์žฅ ๋‚ด ๊ดด๋กญํž˜ ํ”ผํ•ด์ž ๋น„์œจ ๋ณด๊ณ ์— ์˜ํ•˜๋ฉด ๊ฐ„ํ˜ธ์‚ฌ ์ง๊ตฐ์ด 41.3%๋กœ 1์œ„๋ฅผ ์ฐจ์ง€ํ•˜์˜€๋‹ค [3].…”
unclassified